Grain Size Effects on Visible and Near-infrared (0.35–2.5 μm) Laboratory Spectra of Ordinary Chondrite and HED Meteorites - Bryn Bowen; Vishnu Reddy; Mario De Florio; Theodore Kareta; Neil Pearson; Roberto Furfaro; Benjamin Sharkey; Allison McGraw; David Cantillo; Juan A. Sanchez; Adam Battle (The Planetary Science Journal, 2023)
Remote spectral characterization of near-Earth asteroids (NEAs) relies on laboratory spectral calibration to constrain their surface composition, including mineral chemistry and relative mineral abundances. Often these calibrations are based on fine meteorite powders that are representative of regolith observed on large NEAs such as (433) Eros. However, spacecraft observations of smaller NEAs such as (25143) Itokawa, (101955) Bennu, and (162173) Ryugu show surfaces devoid of a thick layer of regolith and instead find variegated landscapes with millimeter-sized particles to meter-scale boulders. Here we present the results of a laboratory study to understand the effects of grain size on the spectral properties of meteorites and how this can impact ground-based characterization of NEAs. Our study focuses on ordinary chondrites (H, L, LL) and HED meteorites, as they comprise ∼90% of all meteorites that fall on Earth. Compared to ordinary chondrites, the spectral band parameters of HED meteorites are less affected by changing grain size. Among the ordinary chondrites, LL chondrites are least affected, but the spectral band parameters and mineral chemistries and abundances for H and L chondrites are most affected by changing grain size. Grain size does not seem to have any significant effect on the taxonomic classification of our meteorite spectra. We also used the Hapke model to investigate trends in single-scattering albedo as a function of grain size and present equations to recover the grain size from a spectrum.